A Comparative Study on Working Capital Management of Tata Motors Limited and Maruti Suzuki India Limited - Dr. Sudip Chakraborty; Shilpi Kumari (International Journal of Engineering and Management Research, 2021)
The automobile industry in India is one of the speedily growing industry. Working Capital Management is important in this industry due to increasing demand and huge investment in this sector requires proper management. Working Capital Management perform a vital role in the success and failure of a business due to its effect on the performance and liquidity. Thereby this study has been undertaken to Comparative analyse working capital management of Tata Motors Limited and Maruti Suzuki India Limited for the period of seven years from 2013-14 to 2019-20. In this study three objectives are set for research. The first one was to assess the impact of working capital on sales, second was to assess the impact of working capital on profitability and third was to evaluate the working capital performance of the companies under study through the use of various financial ratios. The study reflects that the efficiency of working capital management of the companies is influenced by the Liquidity Ratios, Debtor Turnover Ratio, Inventory Turnover Ratio and profitability Ratio.